Treatment of waldenstrom's macroglobulinemia with nucleoside analogues - Dimopoulos, M.A.; O'Brien, S.; Kantarjian, H.; Estey, E.E.; Keating, M.J.; Alexanian, R. (Leukemia and Lymphoma, 1993)
Sixty-eight patients with Waldenstrom's macroglobulinemia were treated either with fludar-abine (28 patients) or 2-chlorodeoxyadenosine (40 patients) and responding patients were followed without further treatment. Both programs were well tolerated and myelosuppression was moderate but reversible. Overall, 35 patients responded including 93% of previously untreated patients, 83% of those relapsing off therapy, 48% of patients with primary refractory disease and 15% of those treated during refractory relapse. With a median follow up of 18 months, only two of 15 previously untreated patients have relapsed whereas the median remission duration and survival of previously treated patients were 38 and 43 months respectively. Fludarabine and 2-chlorodeoxyadenosine are both highly active agents against Waldenstrom's macroglobulinemia, especially when administered early in the disease course. © 1993 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
Keywords: 2-chlorodeoxyadenosine; Fludarabine; Nucleoside analogues; Waldenström's macroglobulinemia